AI’s Capability in Understanding Text Context: Students’ Experiences - Hz, Benni Ichsanda Rahman (LET: Linguistics, Literature and English Teaching Journal, 2024)
This study is aimed at investigating the capability of Artificial Intelligence (AI) in understanding the context on text, based on the users' experience. The research question is formulated: to what extent can AI understand and incorporate contextual context when generating text, through the experiences of participants. The methodology for this study follows a qualitative case study design, as outlined by Baxter and Jack (2008), which allows for an in-depth exploration of the phenomenon—AI's capability in understanding context, through participants' experiences. Data collection is conducted using two primary techniques: questionnaires, to gather quantitative data on participants' perceptions of AI's contextual understanding, and interviews, to obtain deeper qualitative insights. The data from the questionnaires will be analyzed using content analysis, which will categorize and quantify participants' responses. The results of the interviews revealed patterns and meanings related to how AI processes and understands context. The findings have practical consequences for developers and users of AI text-generation software.